A study of the factors influencing yield spread of Malaysian Bond / Fatin Nadia Fatihah Ramli - Ramli, Fatin Nadia Fatihah (2011)
This study was attempt to identify which factors that influencing yield spread of Malaysian Bond, to investigate the relationship between Gross Domestic Product (GDP), interest rate and Inflation rate with yield spread of Malaysian Bond and to examine the most significant factors that influence yield spread of Malaysian Bond. In order to prove this study, researcher collects data for Gross Domestic Product (GDP), interest rate and Inflation rate in DataStream and Department of Statistic Malaysia from third quarter of 1998 until first quarter of 2010 and test by using SPSS program (STATISTICAL PACKAGE FOR THE SOCIAL SCIENCE). This study was being tested using multiple regression technique, correlations analysis, coefficient of determination, standard error of coefficient (t-test), analysis of variance (F-test), Tolerance and Variance Inflation Factor (VIF) and Durbin Watson test. The finding shows that Gross Domestic Product (GDP) and interest rate was significant result. From the finding also, it shows that the inflation rate is not really related with Yield spread of Malaysian Bond. Therefore, the researcher makes suggestion to future researcher to consider for different macroeconomic factors such as money supply, Industry Production Index, KLCI or foreign exchange rate to see the different from the result